Analisis Semiotik dalam Cerpen "Tak Ada yang Gila di Kota Ini" Karya Eka Kurniawan Telaah Lima Kode Roland Barthes - Rahayu, Zahwa; Abdurrahman, Abdurrahman (TSAQOFAH, 2026)
Studies on the use of Roland Barthes’s five semiotic codes in Indonesian literature remain limited, particularly comprehensive analyses that explain how all five codes operate simultaneously within a single text. This study aims to analyze the operation of the proairetic, hermeneutic, cultural, semic, and symbolic codes in the short story “Tak Ada yang Gila di Kota Ini” by Eka Kurniawan and to explain their contribution to the construction of social critique in the narrative. This research employs a descriptive qualitative approach with a textual analysis design, using lexemes, phrases, and sentences as data, which were collected through close reading and note-taking and analyzed using Barthes’s model of semiotic interpretation. The findings show that all of Barthes’s codes appear significantly and mutually reinforce each other: the proairetic code constructs a sequence of exploitative actions, the hermeneutic code generates enigmas surrounding characters’ identities and motives, the cultural code reveals tensions between moral values and economic power, while the semic and symbolic codes intensify the representation of social critique through the connotations and symbolization of the “mad person” character. These results contribute to the development of literary semiotics, particularly in understanding layered structures of meaning in contemporary Indonesian literary works, and underscore the importance of critical reading of symbols and narrative actions in the text, while also opening avenues for further research on the application of Barthes’s codes to other works and media.